IMPROVING THE QUALITY OF STUDENT LEARNING THROUGH FORMATIVE EVALUATIONAT SDN PIR BATEE PUTEH V ARONGAN LAMBALEK, WEST ACEH DISTRICT - Yulia Riechie; Siti Mayang Sari (Sensei International Journal of Education and Linguistic, 2024)
Education is the foundation for the development of a nation which plays an important role in forming individual character, knowledge and skills. The basic education level is an important foundation in the development journey of every student, and the quality of learning at this level greatly determines an individual's future success. One aspect that plays a big role in determining the quality of learning is the evaluation method applied by the teacher. This study aims to determine improving the quality of student learning through formative evaluationat SDN Pir Batee Puteh V, Arongan Lambalek District, West Aceh Regency. This research uses a qualitative approach with descriptive research type. Based on the interview results, it can be seen that the implementation of formative evaluation at SDN Pir Batee Puteh V shows a planned and sustainable approach, with special training for teachers and the use of various evaluation instruments. Teachers actively engage students, provide open feedback, and conduct class discussions. Schools involve parents through regular meetings, providing access to children's evaluation results, and encouraging support at home. Although teachers face challenges of curriculum adjustments, schools overcome them with teacher training and collaboration.